2022
DOI: 10.1177/0271678x221124644
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion in untreated, controlled, and uncontrolled hypertension

Abstract: This study evaluated the association between systemic arterial blood pressure and cerebral perfusion in 740 participants of the UK's largest tri-ethnic study with measurements of cerebral blood flow (CBF) performed using arterial spin labelling MRI. A significant negative correlation between blood pressure, age and CBF was observed across the patient cohort. The lowest CBF values were recorded in the group of patients with hypertension that were prescribed with anti-hypertensive drugs, but uncontrolled on medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…This is in line with previous rat studies that found angiogenic responses in chronic hypertension [69,78,87,88]. We previously showed that cortical blood flow is reduced in chronic hypertensive rats [11], similar to a recent large human MRI study that assessed cerebral blood flow [89].…”
Section: Angiogenesissupporting
confidence: 91%
“…This is in line with previous rat studies that found angiogenic responses in chronic hypertension [69,78,87,88]. We previously showed that cortical blood flow is reduced in chronic hypertensive rats [11], similar to a recent large human MRI study that assessed cerebral blood flow [89].…”
Section: Angiogenesissupporting
confidence: 91%
“…However, recent systematic review and meta-analyses suggest that potential effects of these medications on CBF in otherwise healthy older adults are likely to be minimal. [57][58][59]…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…181,183,214 Under normal conditions, CBF gradually declines with increasing age in both men and women. 189,215 This decline can be accelerated in the presence of hypertension 26,[216][217][218] or conditions such as heart failure. 160 Based primarily on temporal relationships, many studies have suggested that reductions in CBF begin before the onset of cognitive decline but are accelerated in the presence of hypertension (Figure 1).…”
Section: Cerebral Blood Flowmentioning
confidence: 99%
“…160 Based primarily on temporal relationships, many studies have suggested that reductions in CBF begin before the onset of cognitive decline but are accelerated in the presence of hypertension (Figure 1). 160,216,218,219 For example, in a population-based study with an almost 7-year follow-up, there was an association between reductions in CBF and subsequent cognitive deficits. 220 Lower CBF at baseline was associated with an increased rate of cognitive decline, particularly for memory and executive function, and a higher risk of dementia.…”
Section: Cerebral Blood Flowmentioning
confidence: 99%